2013
DOI: 10.14260/jemds/1287
|View full text |Cite
|
Sign up to set email alerts
|

PREVALENCE OF ACUTE RHEUMATIC FEVER (ARF) & RHEUMATIC HEART DISEASE (RHD) IN URBAN SCHOOL CHILDREN OF DISTRICT SRINAGAR

Abstract: Rheumatic Heart Disease (RHD) is still a major public health problem in developing countries such as India. Present study was conducted in urban population of district Srinagar of J&K state (India). A study had been conducted in the same population in 1983 & the prevalence at that time was 5.9 / 1000. The aim of the present study was to know the present status of Acute Rheumatic Fever (ARF) & RHD in the same population since we have observed a significant decline in the attendance of these patients in OPD & wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The survey studies reported from different urban and rural areas in India using auscultation based screening and echocardiography confirmation in suspected cases by different investigators suggests declining trends especially in last decade or so 15, 16, 17, 18,21. The two-point survey study done by our group among school children of Shimla city and adjoining rural area in year 1992-93 and in year 2006–07 using same screening method demonstrated about five fold decline in the prevalence (2.89/1000 to 0.89/1000) 21…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The survey studies reported from different urban and rural areas in India using auscultation based screening and echocardiography confirmation in suspected cases by different investigators suggests declining trends especially in last decade or so 15, 16, 17, 18,21. The two-point survey study done by our group among school children of Shimla city and adjoining rural area in year 1992-93 and in year 2006–07 using same screening method demonstrated about five fold decline in the prevalence (2.89/1000 to 0.89/1000) 21…”
Section: Discussionmentioning
confidence: 96%
“…The number of children with RF/RHD detected in present school-based surveillance system is significantly lower than the figures reported from active surveillance studies in school children. 15, 16, 17, 18, 19 In a survey study of school children aged 5–15 years in government schools of Shimla district in 2007–08 under Gian Vigyan Mission mode project prevalence of RF/RHD was 1.0/1000 (unpublished data).…”
Section: Discussionmentioning
confidence: 99%